2015
DOI: 10.1074/jbc.m114.614222
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes Leading to T7 DNA Delivery upon Interaction with the Bacterial Receptor

Abstract: Background: T7 bacteriophage infects E. coli bacteria; during this process, the tail recognizes the bacterial receptor. Results: Interactions of T7 with rough LPS trigger DNA delivery by promoting changes in the tail tube. Conclusion: E. coli rough LPS act as the receptor in vitro for T7 bacteriophage. Significance: Biotechnological application of bacteriophages as antibacterial agents demands detailed molecular knowledge of bacteriophage infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 43 publications
2
74
0
Order By: Relevance
“…1A), while the incubation with smooth LPS did not affect the DNA content of T7 particles. 11 These results suggested that the inactivation of T7 was due to the release of DNA from the virus capsid triggered by the interaction of the T7 particle with purified rough LPS.…”
Section: Lipopolysaccharides Act As the Main T7 Receptor In Vitromentioning
confidence: 82%
See 4 more Smart Citations
“…1A), while the incubation with smooth LPS did not affect the DNA content of T7 particles. 11 These results suggested that the inactivation of T7 was due to the release of DNA from the virus capsid triggered by the interaction of the T7 particle with purified rough LPS.…”
Section: Lipopolysaccharides Act As the Main T7 Receptor In Vitromentioning
confidence: 82%
“…16 The fact that these processes also take place after interaction of T7 viral particles with purified rough LPS in vitro suggests that this single interaction is able to mimic the main steps of the DNA ejection process during T7 infection of E. coli. Based on these assumptions, Gonzalez-Garcia et al 11 performed a series of in vitro assays to follow DNA ejection rates, and to determine the virus-LPS interaction con- 17 It is interesting to note that the slower Podoviridae DNA release kinetics, as compared with other virus of the Siphoviridae family, 17 might be caused by the simultaneous translocation of the internal core proteins together with the DNA in the case of Podoviridae.…”
Section: Lipopolysaccharides Act As the Main T7 Receptor In Vitromentioning
confidence: 99%
See 3 more Smart Citations